viniterranova
1) a=b 2) ab=a^2 3) ab-b^2=a^2-b^2 4) b(a-b)=(a+b)(a-b) 5) b= a+b
Reminder the first step where b = 2b So,
1=2.
In this case in my opinion the wrong step is that in the third, because you can´t subtract -b^2 from both sides.
Delete
Share
This Question is Closed
ParthKohli
Best Response
You've already chosen the best response.
2
lol why not?
ParthKohli
Best Response
You've already chosen the best response.
2
Transition from step 4-5 is wrong. Guess why!
viniterranova
Best Response
You've already chosen the best response.
0
Tell me ParthKohli.
ParthKohli
Best Response
You've already chosen the best response.
2
Division by zero. Period.
viniterranova
Best Response
You've already chosen the best response.
0
Write step-by-step. plz.
ParthKohli
Best Response
You've already chosen the best response.
2
\[\rm b(a - b) = (a + b)(a - b)\]Since (a - b) = 0,\[\rm 0b = 0(a + b)\]
ParthKohli
Best Response
You've already chosen the best response.
2
But what this thing shows is that it's divided both sides by 0.
viniterranova
Best Response
You've already chosen the best response.
0
thanks